A single-step sequencing method for the identification of Mycobacterium tuberculosis complex species. - Zoheira Djelouadji; Didier Raoult; Mamadou Daffé; Michel Drancourt (PLoS Neglected Tropical Diseases, 2008)
BACKGROUND: The Mycobacterium tuberculosis complex (MTC) comprises closely related species responsible for strictly human and zoonotic tuberculosis. Accurate species determination is useful for the identification of outbreaks and epidemiological links. Mycobacterium africanum and Mycobacterium canettii are typically restricted to Africa and M. bovis is a re-emerging pathogen. Identification of these species is difficult and expensive. METHODOLOGY/PRINCIPAL FINDINGS: The Exact Tandem Repeat D (ETR-D; alias Mycobacterial Interspersed Repetitive Unit 4) was sequenced in MTC species type strains and 110 clinical isolates, in parallel to reference polyphasic identification based on phenotype profiling and sequencing of pncA, oxyR, hsp65, gyrB genes and the major polymorphism tandem repeat. Inclusion of M. tuberculosis isolates in the expanding, antibiotic-resistant Beijing clone was determined by Rv0927c gene sequencing. The ETR-D (780-bp) sequence unambiguously identified MTC species type strain except M. pinnipedii and M. microti thanks to six single nucleotide polymorphisms, variable numbers (1-7 copies) of the tandem repeat and two deletions/insertions. The ETR-D sequencing agreed with phenotypic identification in 107/110 clinical isolates and with reference polyphasic molecular identification in all isolates, comprising 98 M. tuberculosis, 5 M. bovis BCG type, 5 M. canettii, and 2 M. africanum. For M. tuberculosis isolates, the ETR-D sequence was not significantly associated with the Beijing clone. CONCLUSIONS/SIGNIFICANCE: ETR-D sequencing allowed accurate, single-step identification of the MTC at the species level. It circumvented the current expensive, time-consuming polyphasic approach. It could be used to depict epidemiology of zoonotic and human tuberculosis, especially in African countries where several MTC species are emerging.